Perjalanan lima dekad pertama wajah kewartawanan Malaysia, 1966-2016 : MPI 2007, IAM 1974, SEAPC 1966 - Chamil Wariya
On history of journalism in Malaysia; volume commemorating the 50th anniversary of Malaysian Press Institute.